2022
DOI: 10.3889/oamjms.2022.8483
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative EEG Correlates with NIHSS and MoCA for Assessing the Initial Stroke Severity in Acute Ischemic Stroke Patients

Abstract: BACKGROUND: National Institutes of Health Stroke Scale (NIHSS) and Montreal Cognitive Assessment (MoCA) measure stroke severity by assessing the functional and cognitive outcome, respectively. However, they cannot be used to measure subtle evolution in clinical symptoms during the early phase. Quantitative EEG (qEEG) can detect any subtle changes in CBF and brain metabolism thus may also benefit for assessing the severity. AIM: This study aims to identify the correlation between qEEG with NIHSS and MoCA for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
2
2
Order By: Relevance
“…This difference may be attributed to the different participants involved in the two studies, with this study involving healthy subjects and subjects with a history of cerebral infarction and cognitive impairments. Conversely, this study does not align with the previous research conducted by Asmedi et al (2022) which did not find a relationship between MoCA-INA and beta rhythm [28]. Limitation There are certain limitations that must be recognized.…”
Section: Cognitive Function and Qeegcontrasting
confidence: 91%
See 1 more Smart Citation
“…This difference may be attributed to the different participants involved in the two studies, with this study involving healthy subjects and subjects with a history of cerebral infarction and cognitive impairments. Conversely, this study does not align with the previous research conducted by Asmedi et al (2022) which did not find a relationship between MoCA-INA and beta rhythm [28]. Limitation There are certain limitations that must be recognized.…”
Section: Cognitive Function and Qeegcontrasting
confidence: 91%
“…However, the strength of the relationship differs between the two studies. This study shows a weak correlation, while the study by Wang et al showed a significant correlation [27]. This difference may be attributed to the different participants involved in the two studies, with this study involving healthy subjects and subjects with a history of cerebral infarction and cognitive impairments.…”
Section: Cognitive Function and Qeegcontrasting
confidence: 58%
“…EEG provides a widely available, low-cost measure of cortical neurophysiology which can provide predictive electrophysiological markers for monitoring instantaneous and long-term cognitive functioning 18 , 19 . EEG-based indexing of PD-related cognitive functions can generate objective, rapid, and robust measures of cognition with continuous measurements in complex environments.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, EEG-based cognitive assessment that does not require expert administration and is compatible with repeated or continuous measurement would be of great benefit. Changes in EEG activities correlate with cognitive measures such as MoCA and cognitive tests from NIH-Toolbox in various medical conditions 18 , 19 , 23 . However, to date, few EEG-based biomarkers have been found in PD patients that correlate strongly with cognitive performances measured by these tests even though such EEG-based measures can achieve superior assessment of cognitive fluctuations 21 , 23 – 25 .…”
Section: Introductionmentioning
confidence: 99%